Effects of Gynura procumbens extract supplementation on growth performance, carcass traits, antioxidant capacity, immunity and meat quality of meat ducks - Ai, Gaoxiang; Xiong, Pingwen; Chen, Jiang; Song, Wenjing; Song, Qiongli; Xu, Chuanhui; Su, Weide; Zou, Zhiheng; Wei, Qipeng; Chen, Xiaolian (Frontiers in Veterinary Science, 2024)
IntroductionGynura procumbens (Lour.) Merr is a common traditional Chinese medicine with anti-tumor, anti-inflammatory and antioxidant activities. However, no related studies reported the potential application effect of Gynura procumbens on meat ducks. The study aims to investigate the potential effects of Gynura procumbens extract (GPE) supplementation on growth performance, carcass traits, antioxidant capacity, immunity and meat quality.MethodsA total of 480 21-day-old female healthy ducks were randomly allocated to four treatments, each treatment containing six replicates with 20 ducks per replicate. The groups received a corn-soybean basal diet supplemented with 0 mg/kg GPE (CON), 200 mg/kg GPE (GPE200), 400 mg/kg GPE (GPE400), and 600 mg/kg GPE (GPE600), respectively. The entire experiment lasted for 7 weeks.ResultsThe results showed that dietary supplementation with 600 mg/kg GPE significantly reduced the contents of serum urea nitrogen, triglyceride (TG) and total cholesterol (TC). GPE (200, 400, and 600 mg/kg) supplementation effectively reduced the contents of IL-2 and MDA. The levels of immunoglobulin M (IgM) as well as total antioxidative capacity (T-AOC) in GPE600 group dramatically elevated in comparison with the control group. Dietary GPE supplementation considerably increased the moisture content of the breast muscle. Furthermore, dietary supplementation with GPE markedly decreased the water loss rate and shear force.DiscussionWith the ban of antibiotics in poultry production, traditional Chinese medicines have been widely used in livestock and poultry production due to their high efficiency and low toxicity. Gynura procumbens extract GPE as a natural plant origin contains a series of biologically active components, including flavonoids, polyphenols, saponin, tannin and terpenoid. This study indicated that dietary supplementation with GPE can increase serum total antioxidant capacity, regulate immune function and improve meat quality to some extent in meat ducks. The recommended optimal GPE level in the diet of meat ducks is 600 mg/kg according to the results in this study.